2003
DOI: 10.1002/adv.10050
|View full text |Cite
|
Sign up to set email alerts
|

Improved polyurethane dispersion stability via continuous process

Abstract: This paper presents a continuous process for producing waterborne polyurethane dispersion (PUD) with improved shelf life stability. The work also demonstrates that when a typical batch operation fails to produce stable PUD products because of low emulsifier content and/or absence of solvent, the continuous process offers reasonable colloidal stability performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Keyvani7 reported that the waterborne PU modified with acrylic resin had the lowering of cost and the improvements of water resistance, chemical resistance, gloss, hardness, and mechanical properties. So, for the requirements of environmental protection and reducing cost, the polyurethane‐acrylate (PUA) hybrid emulsion has been paid more attention as a type of environment‐friendly material.…”
Section: Introductionmentioning
confidence: 99%
“…Keyvani7 reported that the waterborne PU modified with acrylic resin had the lowering of cost and the improvements of water resistance, chemical resistance, gloss, hardness, and mechanical properties. So, for the requirements of environmental protection and reducing cost, the polyurethane‐acrylate (PUA) hybrid emulsion has been paid more attention as a type of environment‐friendly material.…”
Section: Introductionmentioning
confidence: 99%
“…This process is necessary for the formation of a stable dispersion in water; the final particle size of the dispersion depends on both neutralization and agitation. 2,9,15,16 For all the libraries the controlled addition of TEA was done over a period of 5 or 10 min after the temperature reached 70°C while stirring at 400 rpm. Changing the rate of addition of TEA in one of the libraries, PUD-E, did not have a significant effect on the number of good PUDs formed.…”
Section: Resultsmentioning
confidence: 99%
“…This is because waterborne systems are very sensitive to the factors involved during the development of the coatings and during the application. 2,4 Some of the advantages of waterborne PUDs are low VOC, minimal toxicity and environmental issues, and freedom from flammability and explosion hazards. Another important structural and functional characteristic of waterborne PUDs is the presence of polar ionic groups (typically carboxylate or sulphonate) in the polymer chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel methods for synthesizing PUDs have attracted the interests of researchers. Peter and Arthur and Keyvani first synthesized isocyanate‐terminated prepolymer, and then dispersion and chain extension stages were carried out in a continuous mode to form PUDs . However, there are some differences in their synthesis processes.…”
Section: Introductionmentioning
confidence: 99%